Prevalence of depressive tendencies among college students and the influence of attributional styles on depressive tendencies in the post-pandemic era - Luo, Ming-ming; Hao, Ming; Li, Xu-huan; Liao, Jing; Wu, Chun-mei; Wang, Qi (Frontiers in Public Health, 2024)
Introduction Depression symptoms are prevalent globally, including China, with a notable impact on college students. This study aims to not only estimate the prevalence of depressive tendencies and attributional styles among college students in the post-pandemic era but also explore the relationship between the two factors. The findings of this study can provide new insights into early intervention and support services for individuals exhibiting tendencies toward depression. Methods The survey was administered to college students from various academic backgrounds at a specific university in southern Jiangxi Province by employing two scales to investigate depressive tendencies and attributional styles. Depressive tendency was evaluated using the Patient Health Questionnaire-9 (PHQ-9), while the attributional styles were assessed using the Multidimensional-Multiattributional Causality Scale (MMCS). Univariate analysis and multiple logistic regressions were conducted to identify the related factors of depressive tendency. Results A relatively high (48.9%) prevalence of depression among college students was found in this study. College students with higher grades (OR = 1.574, 95%CI: 1.369–1.810), profession of medicine and allied health sciences (OR = 1.779, 95%CI: 1.203–2.629), experiencing higher study stress (OR = 2.006, 95%CI: 1.601–2.514), and having poor physical condition (OR = 1.527, 95%CI: 1.247–1.869) were identified as risk factors for depressive tendency. The correlation between higher grades and increased learning pressure, coupled with poorer physical condition, heightens the vulnerability of college students to depression. Moreover, the more they attribute these experiences to achievement effort (OR = 0.897, 95%CI: 0.828–0.972), achievement ability (OR = 0.903, 95%CI: 0.838–0.972), and affiliation context (OR = 0.919, 95%CI: 0.860–0.982), the less likely they are to develop depression. Conclusion In the group of college students, especially those in higher grades, profession of medicine and allied health sciences or experiencing high learning pressure and poor physical condition, emphasizing the significance of their mental well-being becomes crucial. Offering suitable support and assistance is essential. Additionally, fostering the cultivation of positive attributional and coping strategies by attributing difficulties to controllable factors and instilling a belief in their ability to overcome challenges can help reduce the risk of depression.